Capturing Tacit Knowledge for Spacecraft Operations in ESOC - Roberta Mugellesi Dow; Siegmar Pallaschke (Journal of Systemics, Cybernetics and Informatics, 2010)

(untitled)
Within the past years, several activities were undertaken towards the introduction of a knowledge management system at ESOC, the European Space Operations Centre. Now the knowledge management activities at ESOC are in a new phase where emphasis is put on knowledge capture. The paper describes the current knowledge management activities at ESOC specifically in knowledge capture and focuses on the developed and adopted methods and on the results obtained related to the process of knowledge capture using video-recording of experts. Furthermore it describes the steps which have been identified for the knowledge capture process: setting expectations and communication rules, structuring and conducting the interviews, preparing the list of questions to encourage the sharing of the tacit knowledge, reviewing the recorded material, etc.